2012
DOI: 10.1002/asia.201101049
|View full text |Cite
|
Sign up to set email alerts
|

Lamellarins as Inhibitors of P‐Glycoprotein‐Mediated Multidrug Resistance in a Human Colon Cancer Cell Line

Abstract: Chemical analysis of a Didemnum sp. (CMB-01656) collected during scientific Scuba operations off Wasp Island, New South Wales, yielded five new lamellarins A1 (1), A2 (2), A3 (3), A4 (4) and A5 (5) and eight known lamellarins C (6), E (7), K (8), M (9), S (10), T (11), X (12) and χ (13). Analysis of a second Didemnum sp. (CMB-02127) collected during scientific trawling operations along the Northern Rottnest Shelf, Western Australia, yielded the new lamellarin A6 (14) and two known lamellarins G (15) and Z (16)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 17 publications
2
44
0
Order By: Relevance
“…Some are found with anticancer activity while others can reverse back multidrug resistance in cancer cells. Lamellarins inhibit the P -glycoprotein whose mechanism includes transporting anticancer agents out of cancer cells and thus making them multidrug resistance [52]. SAR studies concluded many positive and negative factors responsible for anti-tumor activity of lamellarins.…”
Section: Marine Productsmentioning
confidence: 99%
“…Some are found with anticancer activity while others can reverse back multidrug resistance in cancer cells. Lamellarins inhibit the P -glycoprotein whose mechanism includes transporting anticancer agents out of cancer cells and thus making them multidrug resistance [52]. SAR studies concluded many positive and negative factors responsible for anti-tumor activity of lamellarins.…”
Section: Marine Productsmentioning
confidence: 99%
“…119 Several members of the family, especially lamellarin I, reverse multidrug resistance (MDR) by direct inhibition of the P-gp-mediated efflux. 120,121 This pharmacological profile opens the possibility of their use as antitumor agents in resistant cells as well as their use as modulators of the MDR phenotype in combination with other antitumor compounds. Structure-activity relationship studies in the lamellarins 122 showed little tolerance toward changes in the substitution pattern in the natural products and underscored the importance of the methoxy and hydroxyl groups.…”
Section: Non-camptothecin Topoisomerase I Inhibitorsmentioning
confidence: 99%
“…in 1985. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] These lamellarins exhibit a number of interesting biological activities such as potent cytotoxicity against cancer cell lines, 8,9,11,12,[14][15][16][17][18][19][20][21] multi-drug resistance (MDR) reversal activity, 15,16 anti-HIV activity, 11,18,22 topoisomerase I inhibitory activity, 23,24 inhibition of mitochondrial function, [25][26][27][28] and protein kinases inhibitory activity. 29 Lamellarins possess a unique 14-phenyl-6H- [1]benzopyrano- According to X-ray crystallographic analyses of several lamellarins, the aryl group attached to C1 is This paper is dedicated to Professor Dr. Victor Snieckus on the occasion of his 77 th birthday.…”
Section: Up To Now Approximately Fifty Lamellarins Have Been Charactmentioning
confidence: 99%